A demand side management strategy based on forecasting of residential renewable sources: A smart home system in Turkey - Tascikaraoglu, A.; Boynuegri, A. R.; Uzunoglu, M. (ELSEVIER SCIENCE SA, 2014)
The existing electricity systems have been substantially designed to allow only centralized power generation and unidirectional power flow. Therefore, the objective of improving the conventional power systems with the capabilities of decentralized generation and advanced control has conflicted with the present power system infrastructure and thus a profound change has necessitated in the current power grids. To that end, the concept of smart grid has been introduced at the last decades in order to accomplish the modernization of the power grid while incorporating various capabilities such as advanced metering, monitoring and self-healing to the systems. Among the various advanced components in smart grid structure, smart home is of vital importance due to its handling difficulties caused by the stochastic behaviors of inhabitants. However, limited studies concerning the implementation of smart homes have so far been reported in the literature. Motivated by this need, this paper investigates an experimental smart home with various renewable energy sources and storage systems in terms of several aspects such as in-home energy management, appliances control and power flow. Furthermore, the study represents one of the very first attempts to evaluate the contribution of power forecasting of renewable energy sources on the performance of smart home concepts. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Smart home; Demand side management; Renewable energy forecasting; Distributed energy sources; Smart grid; ENERGY-CONSUMPTION; CONTROLLER; SIMULATION; RESOURCE; Construction & Building Technology; Energy & Fuels; Engineering